2020
DOI: 10.1002/agj2.20144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oat and spring pea mixtures on forage characteristics in different environments

Abstract: Forage mixtures including oat (Avena sativa L.) and spring pea (Pisum sativum L. spp. sativum) provide opportunities to optimize forage production with increasing forage quality, relative to single species stands. Under different climate scenarios, adjusting seeding rates of these mixtures may produce variable results in forage quantity and quality. We conducted a 2-yr study at three study sites to evaluate forage characteristics within mixtures of oat and spring pea stands across a semi-arid to subhumid preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The differences in climatic condition between the years affect growing condition, hence pea densities and mixtures' effect on crude protein content changed depending on these factors (Figure 2). As our findings, some researchers (Mao et al, 2012;Yang et al, 2018) reported that growing performance of the plant grown as sole or in mixture showed different performances depending on the differences between years (Carr et al, 2004;Pflueger et al, 2020). Although there are some differences, mixtures showed partly consistent CP content among years, pea densities, and mixtures.…”
Section: Figure 6 Brne Of the Cereals In Different Forage Pea Densitiessupporting
confidence: 76%
“…The differences in climatic condition between the years affect growing condition, hence pea densities and mixtures' effect on crude protein content changed depending on these factors (Figure 2). As our findings, some researchers (Mao et al, 2012;Yang et al, 2018) reported that growing performance of the plant grown as sole or in mixture showed different performances depending on the differences between years (Carr et al, 2004;Pflueger et al, 2020). Although there are some differences, mixtures showed partly consistent CP content among years, pea densities, and mixtures.…”
Section: Figure 6 Brne Of the Cereals In Different Forage Pea Densitiessupporting
confidence: 76%
“…The differences in climatic condition between the years affect growing condition, hence row seeding configuration effect on crude protein content changed depending on these factors (Table 1). The growing performance of the plant grown as sole or mixture had showed different performances depending on the differences between years (Carr et al, 2004;Pflueger et al, 2020). The crude protein content was significantly affected by row seeding configuration in the experiment.…”
Section: Resultsmentioning
confidence: 97%
“…This was expected as the addition of clover in the OC and OCR treatments, particularly in late‐season samples, would have increased CP concentrations due to greater N concentration within the clover tissue and the senescence of oats and radish to form reproductive organs. The inclusion of a legume with a cereal forage, even at relatively low contributions, has been shown to increase CP concentrations of the entire mix (Carr et al., 2004; Han et al., 2013; Pflueger et al., 2020). Mean TDN, however, was greater in O (58.5%), compared to OC (57.2%) and OCR (56.5%; Table 4).…”
Section: Cover Crop Production and Nutritive Valuementioning
confidence: 99%